PARADIGMA BARU DALAM MENGATASI KENAKALAN ANAK REMAJA DI KOTA SAMARINDA (Tinjauan Yuridis UU 35 Tahun 2014 Tentang Perlindungan Anak) - Fitryah Fitryah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT New Paradigm Overcoming the Delinquency of Adolescent Children in Samarinda City (Judicial Review of Law Number 35 Year 2014 on Child Protection). Essay. Faculty of Law. University of 17th August 1945. Samarinda. Supervisor: (1) Ibu Kunti Widyawati, S.H., M.Hum; (2) Mrs. Isnawati, S.H., M.H.In this era of globalization, adolescents are often the center of attention among the public. This is due to the behavior that is considered perverted among them. This can be understood as a behavior that is considered to have exceeded the limits of fairness in the family, school, and community. That way, it is necessary to hold a research that can provide innovation or ideas to solve the problem.This study aims to determine the factors that affect juvenile delinquency and new paradigm in overcoming juvenile delinquency in the city of Samarinda. The method used in this research is normative legal research using normative juridical approach based on Judicial Review of Law Number 35 Year 2014 on Child Protection. In this realm, the researcher uses the source material or material that is in this thesis from the result of the literature. However, Head of Service Unit and Child Protection Polresta Samarinda and SMK Muhammadiyah 3 Samarinda also no less important to support the results of this study.The results of this study concluded that factors that can affect juvenile delinquency in the city of Samarinda there are 3 factors, namely: (1) personal factors; (2) family factors; and (3) social environmental factors and the dynamics of their changes. For the new paradigm that is used to overcome juvenile delinquency in order to keep attention to the rights of adolescent children based on juridical review of Law Number 35 Year 2014 About Child Protection is counseling guidance method through teacher of BP (Guidance and Counseling) that exist in school. This method is oriented towards positive development of the client (adolescent / student).In the end, this research provides advice into two domains: (1) for law enforcement officers, should clarify and include sanctions to the actors who act casually in judging juvenile delinquency; (2) for the parents of a distorted teenager should remain reasonable and not violate the law in educating his or her child. Keywords: juvenile delinquency, new paradigm, and Act No.35 of 2014